Stability of Metal Halide Perovskite Solar Cells. Issue 20 (28th September 2015) - Leijtens, Tomas; Eperon, Giles E.; Noel, Nakita K.; Habisreutinger, Severin N.; Petrozza, Annamaria; Snaith, Henry J.
<x xml:space="preserve">Abstract</x> In recent years, there has been an unprecedented rise in the performance of metal halide perovskite solar cells. They are now in a position to compete on performance with traditional crystalline solar cells, and as such the most pressing questions concern the long term operational stability of this class of solar cell. Here, recent developments in understanding and overcoming stability concerns of metal halide perovskite solar cells are highlighted. An overview of possible instability issues due to electrical, atmospheric, heat, and light stresses is provided and the different implications to the most commonly used device architectures are discussed.